Traversing the context of professional learning communities: development and implementation of Technological Pedagogical Content Knowledge of a primary science teacher. Issue 2 (3rd April 2019) - Cheah, Yin Hong; Chai, Ching Sing; Toh, Yancy
ABSTRACT: Background : Professional learning communities are increasingly recognized for their significance in building teachers' competencies for educational reform. However, the knowledge development cycle of technological pedagogical content knowledge (TPACK) through multiple professional learning communities is not well researched. Purpose : This qualitative case study investigates a primary science teacher's TPACK development in the context of two interdependent learning spaces: a joint-school and a within-school professional learning community. The school's organizational and sociocultural influences on teacher learning are also examined. Participant : Teacher Sean (pseudonym) embarked on a science innovation project after two years of teaching in a Singapore mainstream school. He was tasked to integrate mobile-based inquiry learning and visible thinking pedagogical approaches, and to pilot the designed lessons for a primary three class. Design and methods : A case-study approach involving multiple sources of data with cultural historical activity theory as the analytical lens was employed, to unpack the complementary and contradictory interactions across different interrelated activity systems. The purpose was to understand the (mis)alignments within and between the two professional learning communities. Results : The findings indicate that Sean's ( subject ) learning from the joint-school professional learning community to the within-school professional learning community faced multiple tensions that hindered his TPACK development ( object ). He faced difficulty in manipulating tools (technology and visible thinking routines) to translate the joint-school co-designed lessons into classroom implementation. Additionally, the volatility of the school's organizational routines ( rules ) and the lack of communicative leader–teacher partnership ( division of labor ) did not afford sufficient infrastructure or instructional support. Conclusions : Interactions between the teacher's personal and contextual factors inhibited the designed TPACK from being implemented successfully. For ambitious pedagogical undertakings as illustrated in this case, more perceptive and synergistic organizational design thinking is needed to support beginning teachers' TPACK development.